Knowledge And Self-Efficacy Of Teachers And Parents In Giving First Aid To Children When Choking In Paud Banjarmasin - Dyah Trifianingsih; Sapariah Anggaraini (Sean Institute, 2023)
Choking causes children to have difficulty breathing, which, if left too long, the body can experience a lack of oxygen, resulting in death. Knowledge and skills are needed for teachers and parents, especially those with early childhood, in the proper handling of choking to increase success and survival rates. Good knowledge makes individuals more confident in the actions they will take. Self-efficacy influences the steps a person will take. This study aimed to determine the relationship between teachers' and parents' knowledge and self-efficacy in providing children first aid when they choke at Kindergarten Pembina Banjarmasin. This study used an observational research method with a cross-sectional approach. Data collection tool in the form of a questionnaire. The sample used in this study was 83 respondents (consisting of 12 teachers and 71 parents of students). Data analysis will be carried out using univariate analysis with a frequency distribution to see the demographics of respondents and bivariate analysis with chi-square. The results obtained were that the majority of 78.3% of respondents had good knowledge, 80.7% of the majority of respondents had high self-efficacy, and there was a significant relationship between Knowledge and Self-efficacy of teachers and parents in providing first aid for children when choking (p-value 0.000; α 0.05). It is vital to increase knowledge which can later increase self-efficacy for teachers and parents in providing choking treatment for children.